Penggunaan Design Thinking Pada Inovasi Produk Jasa Cabut Kost - Mochammad Rifky Pamungkas; Iwan Sukoco (Program Studi Manajemen Fakultas Ekonomika dan Bisnis Universitas Majalengka, 2022)
The condition of the Covid-19 pandemic in Indonesia to date has had an impact on all business actors, therefore all actors from various business fields need to make a breakthrough or innovation in order to be able to compete and stay afloat. The problem now is that all must be required to provide appropriate problem solving and be able to be implemented properly in responding to all perceived obstacles and challenges. One of the methods that can be used and provide solutions to current conditions is design thinking. Design thinking is a discipline that uses designer sensibilities and methods to match people's needs with what is technologically feasible and what is feasible according to a business strategy can be transformed into customer value and market opportunities, by analyzing five stages which include empathize, define, ideate, prototypes and tests. The purpose of writing this article is to explain the use of design thinking in the Logistics Service business of Cabut Kost with a qualitative descriptive method with the aim of providing a description or summary of a situation or phenomenon that is currently happening by using scientific procedures to answer actual problems. The results obtained are that the application of design thinking can be used as a reference method for Cabut Kost in developing the business that is being undertaken. As far as the analysis is concerned, design thinking can be a method for developing a strategy to build a brand name for Cabut Kost.